Case Report: Multimodal management of a rare pediatric astroblastoma using proton beam therapy and Gamma Knife radiosurgery—a case report and literature review - Zhang, Xijia; Wang, Xinfa; Ning, Weihai; Liang, Jianfeng; Jin, Yonglong; Nie, Yuqian; Wang, Jie; Wang, Zishen; Wang, Wei; Zhao, Jun; Kong, Jingjing; Yang, Lu; et al. (Frontiers in Oncology, 2025)
IntroductionAstroblastoma is an infrequent glial tumor, with the MN1-altered subtype recognized in the 2021 WHO classification. This report details the management of a 4-year-old girl diagnosed with CNS WHO Grade 3 MN1-altered astroblastoma, also found to have a heterozygous BRCA2 mutation. We highlight a sequential multimodal treatment approach involving proton beam therapy (PBT), targeted chemotherapy with a PARP inhibitor, and subsequent salvage Gamma Knife radiosurgery (GKRS).Main symptoms and findingsThe patient presented with right lower extremity weakness and gait disturbance. Initial treatment involved maximal safe resection followed by adjuvant PBT (craniospinal irradiation 36 Gy, local boost to 54 Gy). PBT was selected for its dosimetric advantages, notably minimizing radiation dose to surrounding healthy tissues, thereby reducing potential acute toxicity and long-term risks compared to conventional photon therapy. Despite this, residual tumor persisted. Following the discovery of a BRCA2 mutation, the PARP inhibitor fluzoparib was administered, which was associated with temporary disease stabilization.Diagnoses, interventions, outcomesAfter a second resection confirming residual disease, salvage stereotactic radiosurgery (SRS) using Gamma Knife (30 Gy in 5 fractions) was administered to the remaining lesions. The patient has demonstrated sustained local control with no tumor progression for over 18 months post-SRS, with only mild, asymptomatic perilesional edema and no neurological deficits.Conclusion - Take-away lessonThis case suggests that leveraging the tissue-sparing benefits of initial PBT may enable effective salvage SRS for managing residual or recurrent high-grade pediatric astroblastoma. Furthermore, it highlights the potential role of molecular profiling to guide targeted therapies in these rare tumors.